Improving Living Conditions of Widows: The Role of Sister Connection Organization in Burundi - Alexis, Ndabarushimana; Francine, Dushime (European Scientific Journal, ESJ, 2018)
This paper focuses on the role of Sister Connection organization in improving the living conditions of Burundian widows. Specifically, it shows how received assistance has contributed to improving the living conditions of widows. It also shows different constraints that Sister Connection is facing in its effort of supporting widows. It further allowed us to know the suggestions that widows and the management of Sister Connection have. We opted for qualitative approaches with the use of the interview guide, and quantitative approaches with the use of a questionnaire administrated indirectly to the widows sponsored by Sister Connection. 96 widows have been selected using Bouchardâ€™s technique. An interview protocol was conducted by the National Director and a questionnaire was administered to the 96 widows. Data findings were analyzed using the Statistical Package for the Social Sciences (SPSS). The â€œfamily systems theoryâ€ was chosen and it allowed us to understand how the solidarity that naturally characterizes Burundian families is broken at the death of a spouse and how other family members react to widows in Burundian society. Results showed that living conditions have been improved by the financial and spiritual assistance that the widows received from Sister Connection. Furthermore, the majority of widows have benefited shelter from Sister Connection. Despite all this effort, a significant number of widows assisted by Sister Connection are illiterate, and this presents a challenge to communicate with them whether itâ€™s through written communications or simply explaining certain things or communicating ideas. Training or teaching them becomes a challenge as they donâ€™t easily pick up on things or understand as fast as they could. Widows live far from each other. In fact, some live in isolated areas which make it difficult to reach them and know their needs on a regular basis.